Pengaruh Model Pembelajaran Kooperatif Tipe Talking Stick Terhadap Kemampuan Komunikasi Matematis Siswa Kelas VIII pada Materi Relasi dan Fungsi di MTsN 1 Mataram Tahun Pelajaran 2019/2020 - Nurhayatun Nupus Ayat; Sudi Prayitno; Syahrul Azmi (Indonesian Publication Center, 2021)
This research aims to (1) know the difference in student’s mathematical communication skill who using cooperative learning model talking stick type with the student’s who using lecture learning model and (2) know how much influence the cooperative learning model talking stick type on student’s mathematical communication skills. The subjects in this study are class VIII.4 as a control class and class VIII.7 as an experimental class. Amount of students at each class are 38 students. The instrument that used in this research are : student worksheet, observation sheet teacher activities, and mathematical communication test questions are in the form of descriptive questions. The mathematical communication test is divided into two parts, they are pretest and post test. After implementing the learning process using the control class nor experimental class with different treatments, it can be seen that mathematical communication skill of student who learn to use coopertive learning model talking stick type better than the students who learn to use lecture learning model. The results of data analysis improvement in students mathematical communication skill can be seen from the N-gain mean on experimental class who high category and the N-gain mean on control class who low category. Thus it can be seen that coopertive learning model talking stick type is significant influential and can improve students mathematical communication skill.